Three VCP Mutations in Patients with Frontotemporal Dementia. - Wong, Tsz Hang; Pottier, Cyril; Hondius, David C; Meeter, Lieke H H; van Rooij, Jeroen G J; Melhem, Shami; van Minkelen, Rick; van Duijn, Cornelia M; Rozemuller, Annemieke J M; Seelaar, Harro; Rademakers, Rosa; van Swieten, John C (J Alzheimers Dis, 2018)
Valosin-containing protein (VCP) is involved in multiple cellular activities. Mutations in VCP lead to heterogeneous clinical presentations including inclusion body myopathy with Paget's disease of the bone, frontotemporal dementia and amyotrophic lateral sclerosis, even in patients carrying the same mutation. We screened a cohort of 48 patients with familial frontotemporal dementia (FTD) negative for MAPT, GRN, and C9orf72 mutations for other known FTD genes by using whole exome sequencing. In addition, we carried out targeted sequencing of a cohort of 37 patients with frontotemporal lobar degeneration with Transactive response DNA-binding protein 43 (TDP-43) subtype from the Netherlands Brain bank. Two novel (p.Thr262Ser and p.Arg159Ser) and one reported (p.Met158Val) VCP mutations in three patients with a clinical diagnosis of FTD were identified, and were absence in population-match controls. All three patients presented with behavioral changes, with additional semantic deficits in one. No signs of Paget or muscle disease were observed. Pathological examination of the patient with VCP p.Arg159Ser mutation showed numerous TDP-43 immunoreactive (IR) neuronal intranuclear inclusions (NII) and dystrophic neurites (DN), while a lower number of NII and DN were observed in the patient with the VCP p.Thr262Ser mutation. Pathological findings of both patients were consistent with FTLD-TDP subtype D. Furthermore, only rare VCP-IR NII was observed in both cases. Our study expands the clinical heterogeneity of VCP mutations carriers, and indicates that other additional factors, such as genetic modifiers, may determine the clinical phenotype.